Le reti della comunicazione politica Tra televisioni e social network - CIONI, Elisabetta; MARINELLI, Alberto (Strumenti per la didattica e la ricerca, 2010)
In the contemporary scene, alongside the crisis of political communication and the traditional forms of participation, the transformation of the formats and languages of telepolitics and the increasingly more widespread access of the citizens to interactive platforms that liberate them from the role of mere spectators of the political debate, have come to assume major significance. This book proposes an approach of meditation and mixed methods research, already validated within the framework of the project «Against political communication. Rethinking participation in the age of the old and new media» (PRIN 2007). The aim is to explore the ways in which political communication is currently exploiting the media ecosystem, and the role of this new media equilibrium in the construction of political concepts and political participation on the part of the citizens.